Three new species of the genus Sternoppia (Acari: Oribatida: Sternoppiidae) from Ecuador - Ermilov, Sergey G.; Sandmann, Dorothee; Marian, Franca; Maraun, Mark (Zootaxa, 2013)
Three new oppioid mite species of the genus Sternoppia, S. paraincisa sp. nov., S. paramirabilis sp. nov. and S. fissurata sp. nov., are described. Sternoppia paraincisa sp. nov. is most similar morphologically to Sternoppia incisa Balogh & Mahunka, 1977 from Bolivia, however, it differs from the latter by smaller body size, presence of notogastral setae c, lo-cation of lyrifissures ia, presence of granules on anal plates, and setiform sensilli. Sternoppia paramirabilis sp. nov. is most similar morphologically to Sternoppia mirabilis Balogh & Mahunka, 1968 from Argentina, however it differs from the latter by larger body size, presence of two or three sensillar branches only, and long interlamellar setae. Sternoppia fissurata sp. nov. differs from all species of the genus by the nine pairs of notogastral setae, location of lyrifissures iad in inverse apoanal position, and the presence of large tectum on anterior part of ventral plate. Sternoppia brasiliensis is for the first time recorded in Ecuador. An identification key to all known species of Sternoppia is provided.